A numerical and experimental seismic study on the ductile tubular elements and their performance in Y-Shaped braces. (July 2022) - Solaimani Nezhad, Mohammad Reza; Mahmoudi Sahebi, Mussa
Abstract: Despite having appropriate architectural performance, high strength, and acceptable stiffness, steel Y-shaped braces still demonstrate insufficient ductility. Moreover, the risk of buckling, especially in some of the longest members, can be counted as another deficiency in such systems. One of the methods to alleviate these demerits is employing dampers (such as ductile elements) inside the diagonal members to improve system ductility as a result of their plastic deformations. This could result in a reduction in buckling risk and energy dissipation. For this purpose, in this research, five different types of ductile tubular elements, including a tube with a fixed width, variable (dumbbell-shaped), with stiffener and increasing the thickness at the joint of the ring was used. First, each of the proposed elements was analyzed and their results were compared, then two samples of them were tested for verification. In order to evaluate the proposed system, a one-story single-span frame having a Y-shaped brace has been selected, and the elements were installed on one of the diagonal members of the brace. Then its performance under two various circumstances, including with and without ductile elements, has been studied. In order to assess the reciprocating behavior of the system, an incremental cyclic loading has been employed. Stiffness, strength, and energy absorption are the three different criteria that have been considered for comparison of seismic capacities of the two models. The findings have revealed that employing ductile elements, on average, can enhance strength, stiffness, and energy absorption by 33%, 30%, and 20%, respectively.